Atomic force microscopy investigations of peptide self-assembly - Sedman, Victoria L. (2006)
The ability of short peptide fragments to self-assemble in isolation as amyloid and amyloid-like structures has prompted their use as model systems for the study of amyloid formation and recently also for their utilisation as novel nanofibrillar material. The atomic force microscope (AFM) is used here to investigate the self-assembly of two peptide systems and the development of strategies to directly manipulate and control the structures they form.